2023
DOI: 10.1155/2023/2895892
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Comparison of Fracture Resistance of Severely Damaged Primary Anterior Teeth Restored with Different Post and Core Systems

Abstract: Objectives. This study aimed to compare the fracture resistance (FR) of severely damaged primary anterior teeth restored with five different post and core systems. Materials and Methods. This in vitro, experimental study evaluated 60 extracted primary maxillary central incisors. The teeth were horizontally sectioned at 1 mm above their cementoenamel junction (CEJ), underwent pulpectomy, and their root canals were filled with Metapex paste. After post space preparation and sealing of root fillings with light-cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…In line with this study, Alamdari et al (2023) revealed that Fiber post and EverX Flow core increased fracture resistance of restored incisors more than Bulk fill composite post and core, EverX Flow post and core, Fiber post and Bulk fill composite core, and Conventional composite post and core. Also, Uctasli et al (2021) assessed fracture resistance of restored anterior permanent teeth with different post and core systems using either Grandio Core or EverX Flow as post-luting materials.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In line with this study, Alamdari et al (2023) revealed that Fiber post and EverX Flow core increased fracture resistance of restored incisors more than Bulk fill composite post and core, EverX Flow post and core, Fiber post and Bulk fill composite core, and Conventional composite post and core. Also, Uctasli et al (2021) assessed fracture resistance of restored anterior permanent teeth with different post and core systems using either Grandio Core or EverX Flow as post-luting materials.…”
Section: Discussionsupporting
confidence: 89%
“…The rationale behind placement of PFC final restoration instead of crown was that crown could mask fracture resistance of post and core foundation ( Uctasli et al, 2021 ). The loading force was applied to mid-palatal surface at oblique angle (148°) to long axis of restored incisors to simulate normal incisal force ( Alamdari et al, 2023 ). In addition, applying force at this angle represents worst-case scenario of fracture resistance as it places heavy stress on coronal portion of incisor as well as post-root canal interface ( Fráter et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These factors make Metapex a material that is widely used for primary tooth root fillings. 21,22,23,24 Several authors used post's drill to prepare the post space. 14,18,21 In our study, the space for the post was created using a post's drill of 1.5 mm diameter, in which a stopper was attached to the drill to ensure that 3 mm of the canal was prepared to receive the post.…”
Section: Asdj Ain Shams Dental Journalmentioning
confidence: 99%